PENGARUH CORPORATE GOVERNANCE, LEVERAGE, DAN PROFITABILITAS TERHADAP FREE CASH FLOW PADA PERUSAHAAN PERBANKAN DI INDONESIA - Wahyudi; Madani hatta (UNIB Press, 2023)
This study aims to prove the effect of corporate governance, leverage, and profitability on free cash flow by using independent variables, corporate governance, leverage, and profitability, corporate governance was assessed using internal mechanism in the form of a board of commissioners and audit committee calculated based on the effectiveness of the board of commissioners and audit committee. Samples in research this is the company's banks in Indonesia which is listed on the Stock Exchange Indonesia (BEI) in the years 2015 to 2018 and consists of 33 companies . The data used in this study are secondary data, obtained from financial reports from the website www.idx.co.id. The data collection method uses purposive sampling technique. This study uses a quantitative approach. Data were analyzed using regression linear multiple use device software SPSS version 25. The results show that corporate governance has no effect on the level of free cash flow, while leverage and profitability have a positive effect on the level of free cash flow.